Environmental pollution, population aging and social medical insurance fund expenditure - SI, XU (Advances in Social Sciences Research Journal, 2021)
Although China’s economy has maintained rapid growth since 21st century, the problem of environmental pollution has become increasingly serious. Environmental pollution has a serious impact on people in all aspects of clothing, food, housing and transportation. Based on the panel data of 31 provinces and regions in China from 2005 to 2017, this paper establishes a fixed-effect model and divides China into three regions of central, east and west and analyzes the impact of environmental pollution and the population aging on the expenditure of China’s social medical insurance funds (SMIF). The study found that the more severe environmental pollution, the worse health status of the residents, then induces the higher SMIF; the more serious aging of population, the higher risk of disease and cause higher SMIF. It is recommended to innovate clean energy technologies, increase environmental governance, in order to reduce health care expenditures and restrain the increase of the health care cost.